Computerized assessment of pain drawing area: A pilot study - Anna Wenngren (Dove Medical Press, 2009)
Anna Wenngren, Britt-Marie StålnackeDepartment of Community Medicine and Rehabilitation, Umeå University, SwedenAim: To investigate if pain area in patients with chronic pain could be measured by a computerized assessment on previously marked pain drawings on paper figures and to analyze the further application of the method.Methods: Seventy-two patients (54 women and 18 men) who were admitted to Umeå University Hospital during 2003 for assessment of chronic pain answered a set of questionnaires (pain intensity on the visual analog scale [VAS], disability on the Disability Rating Index [DRI], life satisfaction on the LiSat-11) and filled in pain drawings on paper figures of the human body. The pain drawings were later analyzed by using computerized assessment.Results: Women marked a greater pain area than men, but the difference was not significant (p = 0.433). No significant difference was shown for the previous seven days between men and women on the VAS (p = 0.914), DRI (p = 0.493), or LiSat-11 (p = 0.124). A statistically significant correlation was found between pain area and VAS for the previous seven days (r = 0.250; p = 0.046). Pain area was statistically significantly correlated to the DRI (r = 0.336; p = 0.014) and close to negatively correlated to the LiSat-11 (r = -0.687; p = 0.057).Conclusion: This pilot study shows that pain drawing area could be measured by a computerized assessment of pain drawings. The method points to the possibility of relating pain area with other instruments. In the present study, an association between the patients’ pain drawing area and pain intensity and between pain area and level of activity was shown.Keywords: musculoskeletal pain, screening, pain drawing, computerized assessment